Promoting gender equality in the Provincial Administration of the Western Cape : an appraisal based on perceptions of gender focal persons and the Head of the Western Cape Office on the Status of Women for Gender Equality - Adams, Ubanesia Lolita (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2001.